Learning Safety And Its Effects On Workplace Among Construction Workers In Malaysia - Hassan, Maria; Mohd Zin, Sufri; Abiddin, Norhasni Zainal; Rahim, Rohani Abdul (Universiti Sains Malaysia, 2016)

(untitled)
The 11 Malaysia Plan exhibit the GDP increase in almost all main sector including construction that increased from 3.4% (2010) to 4.5% (2015). Robust activities in the infrastructure and residential subsectors are expected to spur a double-digit growth of 11.1% in the construction sector. Job created by construction sectors between 2011-1015 is 78,000 (4.3%) of other jobs creation by sectors. While the labour productivity for this sector is expected to maintain at estimated 9.6% (per anum) (2011-2015) to 9.6% (per anum) (2016-2020). Safety experts estimate that 80-90% of all industrial accidents are attributable to ‘human factors’ on that point, construction workers need to learn about safety to avoid any accidents that may occur while working. Training and provision of information on Safety culture, laws and leadership behaviour will help promote commitment to safety and encourage their subordinates to value safety as a fundamental goal. In Malaysia, issue of safety performance in construction industry are very frequent being raised up by government, civilians, and even employees and it is not uncommon for construction stakeholders, to concentrate exclusively on completing projects to the required quality standard with the minimum time and cost. Safety is more often seen as secondary concern. On that reason, it is the main purpose of this study is to identify main factors which contribute to safety performance and provides a continuous approach to reduce risk and potential hazard through workplace learning. It will also dwell on how learning safety at workplace can generate awareness and enhance their work performance. Employees should be given safety information and safety culture or climate of an organization, can be nurtured through good leadership and safety practice. Zero Incident Protocol (ZIP) is a workplace safety training program designed to achieve zero safety incidents. As a result, organization are able to avoid paying higher worker’s compensation costs for injuries sustained at work, and maintain a reputation of corporate responsibility, and trained productive workforce.